Degarelix and its therapeutic potential in the treatment of prostate cancer - Christian Doehn; Martin Sommerauer; Dieter Jocham (Clinical Interventions in Aging, 2009)
Christian Doehn, Martin Sommerauer, Dieter JochamDepartment of Urology, University of Lübeck Medical School, Lübeck, GermanyAbstract: Degarelix is a gonadotropin-releasing hormone (GnRH) antagonist for the treatment of patients with prostate cancer in whom hormonal therapy is indicated. Two phase II trials and one phase III have been published as full papers in the literature. In the dose-finding phase II studies an initial dose of 240 mg degarelix sc followed by a monthly injection of 80 mg or 160 mg degarelix sc was sufficient to keep testosterone levels ≤ 0.5 ng/ml. In a phase III trial it was demonstrated that degarelix was not inferior (in terms of testosterone suppression and prostate-specific antigen [PSA] decline) compared to standard hormonal therapy, ie, a GnRH agonist such as leuprolide. In fact, degarelix was associated with a faster testosterone suppression and PSA decline than leuprolide. Adverse events such as pain at the injection site (40% vs <1%) and chills (4% vs 0%) were more commonly associated with degarelix. Also, degarelix is currently only available as one-month depot whereas in daily practice three-month depots (of GnRH agonists) are the preferred regimen. However, degarelix was recently approved by the US Food and Drug Administration for the treatment of advanced prostate cancer.Keywords: prostate cancer, hormonal therapy, GnRH antagonist, degarelix, testosterone, flare